MANAJEMEN PENGELOLAAN RETRIBUSI PASAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA KENDARI - La Ode Muhammad Elwan (Universitas Halu Oleo, 2019)
This study aims to find out how the management of market retribution in increasing Regional Original Revenue in the Lapulu market Kendari City. The approach of this study is a qualitative approach with a type of descriptive qualitative research. The technique of collecting data is done through observation, interviews, and documentation. The data analysis technique used consists of data collection, data reduction, data presentation and conclusion drawing.The results of this study indicate that: planning in terms of setting targets that have been arranged is optimal. This can be seen from the determined and implemented stages of targeting that are carried out every year, but the achievement of targets has never been fulfilled due to lack of awareness of traders or mandatory retribution in terms of paying retribution. The conclusion of the study was that the implementation of market retribution management in increasing Regional Original Revenue in the Lapulu market in Kendari City was not effective due to the lack of intensive collection of mandatory levies, delinquent payment of levies by traders for various reasons so that the realization of market retribution did not reach the planned target.